Gabriel Marcel’s tragic humanism: human being in a broken world - Urabayen Pérez, Julia (Estudios de Filosofía, 2010)
In this paper, I deal with the philosophy of Gabriel Marcel, as a reflection on the human being which is, in the end, a kind of humanism. It is nonetheless a tragic one. He thought about the human being as a valuable being but with the capacity to self-destruct. This capacity of degradation is so far reaching that it has broken the world in which we live. But Marcel’s picture of the Western Industrialized Civilization, as we can see in this article, is not a pessimistic one because, even if the best conditions are not present, it is always possible to recover the wisdom, the skill to think and to control the technology. That’s why in this article, I will begin with a description of Marcel’s concrete philosophy, then I will explain his anthropology and I will end with an exposition of his analyses of the crisis which the agonizing human being is suffering as a result of God’s death.